Independent Contractors, IPros, and Freelancers: New Puzzle Pieces in a Conceptual Jungle - Knapp, Michael; Sawy, Alina; Bögenhold, Dieter (Senate Hall, 2021)
Highly skilled and qualified workers represent a growing group among the solo self-employed across numerous countries. They provide knowledge-intensive services in different occupational, organisational, spatial and temporal contexts and often in hybrid forms of work and employment. Understanding the heterogeneity within this labour market group requires more knowledge and awareness of its characteristics and peculiarities, laying the foundation for the development of clearer definitions and distinctions. The terms used to describe this labour market group are manifold and often not clearly defined and delimited. A better understanding of the actors helps to develop more efficient analytical but also policy-aimed implications to support this group with directly targeted actions. In this paper, we compare the terms used most commonly and often synonymously in the literature -Independent Contractor, Independent Professional (IPro), and Freelancer- and try to point out the differences and similarities between them. It becomes apparent that these terms are not identical, but rather refer to different concepts, namely the business side, the occupational dimension and the work relationship.
Keywords: independent contractor|independent professional|freelancer|Ipros|solo selfemployment|knowledge work|professional services